The Effect of Constructivism-Based STEM on Students' Creative Thinking Skills in Biotechnology Learning - Yustina Yustina; Imam Mahadi; Zulfarina Zulfarina; Oky Priawan; Diana Anggraini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Fish feed biotechnology is fish pellets produced through the fermentation process of mustard greens, fats, and used cooking oil from waste containing vegetable nutrients. The results of this preliminary research were developed into leaflets and booklets as teaching materials for student learning guides through the constructivism-based STEM approach. This research was conducted at SMP Purnama Pekanbaru from February to April 2020 with a one-group pretest-posttest experimental research design. The research subjects were 25 ninth-grade students who took biotechnology extracurricular activities. The data were collected using the students' creative thinking ability test sheets. Scores and mean scores of data were calculated, tabulated, and analyzed descriptively. The research objective was to analyze the effect of the constructivism-based STEM approach on students' creative thinking skills. The results showed that learning using the constructivism-based STEM approach effectively improved students' creative thinking skills in biotechnology learning in recycling waste into fish pellets.